2011
DOI: 10.4236/gm.2011.13013
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Clayey Soils from Congo and Physical Properties of Their Compressed Earth Blocks Reinforced with Post-Consumer Plastic Wastes

Abstract: Physical properties of compressed earth blocks reinforced with plastic wastes are compared to those of nonreinforced ones. These bricks are made with two clayey soils from two deposits of Congo located in Brazzaville and Yengola. Mineralogical and geotechnical analysis revealed that the soil of Brazzaville is mainly composed of <i>kaolinite</i> whereas that of Yengola is a mixture of <i>kaolinite</i> and <i>illite</i>. The amounts of clay (46 and 48%, respectively) are highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 25 publications
(37 reference statements)
1
23
0
Order By: Relevance
“…On the basis of ecological metrics, natural fibers are preferable for CSEB reinforcement because of their being derived from renewable resources that are generally readily available at affordable costs. However when untreated, the fibers may have a negative impact on the mechanical properties of matrices (Elenga et al 2011). The highly alkaline environment created through OPC hydration degrades untreated fibers, which negatively affects the durability of concrete (ACI 544.1R, 1996).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…On the basis of ecological metrics, natural fibers are preferable for CSEB reinforcement because of their being derived from renewable resources that are generally readily available at affordable costs. However when untreated, the fibers may have a negative impact on the mechanical properties of matrices (Elenga et al 2011). The highly alkaline environment created through OPC hydration degrades untreated fibers, which negatively affects the durability of concrete (ACI 544.1R, 1996).…”
Section: Introductionmentioning
confidence: 98%
“…Studies investigating these parameters use both natural and synthetic fibers. It has been demonstrated that sisal (Namango 2006), coconut fiber (Khedari et al 2005;Obonyo, 2011), straw (Binici et al 2005), polyethylene (Elenga et al 2011) can all be feasible options. On the basis of ecological metrics, natural fibers are preferable for CSEB reinforcement because of their being derived from renewable resources that are generally readily available at affordable costs.…”
Section: Introductionmentioning
confidence: 99%
“…Fiber-reinforced blocks can withstand higher stresses by absorbing high amounts of energy making them particularly important in earthquake prone regions [8]. It has been demonstrated that sisal [11,12], coconut fiber [13][14][15], straw [16], polyethylene [10], jute [17,18], are all feasible options for CEB reinforcement. Improvement in ductility is widely accepted as a key benefit of fiber reinforcement in soil-cement composites.…”
Section: Introductionmentioning
confidence: 99%
“…Both natural (obtained from plants and animals) and synthetic fibers are used to reinforce soils for CEB production [7]. The inclusion of fibers into soil-cement mixes for CEB production creates a network of fibers, which improves tensile and shearing strengths, and also helps reduce shrinkage [7][8][9][10]. Fiber-reinforced blocks can withstand higher stresses by absorbing high amounts of energy making them particularly important in earthquake prone regions [8].…”
Section: Introductionmentioning
confidence: 99%
“…To further improve its mechanical properties and, at the same time, reduce waste, researchers are reinforcing it with natural fibers as they show a significant result in post-peak load deformation behavior. The use of fiber reinforcement into CSEB production creates a network of fibers that prevents cracking of the soil resulting from shrinkage and improves tensile and shearing strengths [2], [3]. The inclusion of fibers into CSEB results to resistance towards higher stresses by absorbing high amounts of energy, making them particularly important in earthquake prone regions [4].…”
Section: Introductionmentioning
confidence: 99%